Optical and dielectric properties of diamond-like carbon thin films prepared by DC-PECVD method [electronic resource] - Sonam Tshomo, 1985- (2012)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2012